Venomous snake bite: A case report of limb loss from a neglected bite and review of literature - Adejumo AA; Alegbejo-Olarinoye MI; Adejumo AM (Ibom Medical Journal)
Background: Venomous snake bites have been reported in many climes across the globe with attendant morbidity and mortality. Many people still fall victim to this menace largely from occupational hazards and some socio-cultural practices. This study presents a patient who suffered limb loss from neglected snake bite and a review of the existing body of literature on snake bite management including current concepts and future trends.